Idiosyncratic Factors in Defense Policy Formulation: An Analysis of Prabowo Subianto's Role in Indonesia's Optimum Essential Force 2025 - Muhammad Zhafran Abiyyu; Shabrina Khalisah Ibrahim (Genesis Law and Social Sciences, 2026)
This study analyzes the influence of Prabowo Subianto's idiosyncratic characteristics on the formulation of Indonesia's Optimum Essential Force (OEF) 2025 defense policy. Despite growing scholarly interest in Indonesian defense modernization, existing literature predominantly emphasizes structural and institutional explanations while under examining the role of individual leadership. Drawing on Foreign Policy Analysis, this study employs Leadership Trait Analysis (LTA) based on Hermann's framework and process tracing to construct and verify causal chains between Prabowo's personal characteristics and specific OEF 2025 policy decisions. Analysis of spontaneous public statements identifies four dominant traits: high need for power, high belief in ability to control events, high self-confidence, and high ingroup bias combined with medium-high distrust of others. Process tracing demonstrates that these traits causally contributed to the centralization of acquisition decision-making, the mandatory inclusion of technology transfer clauses, the ambitious defense budget targets, and platform preferences reflecting limited power-projection ambitions. The findings indicate that the qualitative shift from the Minimum Essential Force to OEF 2025 cannot be explained by regional structural pressures alone; within this case, the idiosyncratic variable functions as a necessary component of the explanation. The study contributes the first systematic individual-level account of Indonesian defense policymaking and illustrates the analytical value of leadership variables in explaining departures from established policy trajectories.